(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article studies the mechanism of generating potential difference in the range of 12-24 V DC using the thermoelectromotive force arising at the boundary of two dissimilar conductors. The experimental conditions are considered, including the choice of materials, temperature conditions, the influence of the conductor cross-section, and the use of transformers to increase the output voltage. An analysis of the feasibility of this economic approach is carried out, taking into account some costs.